Effect of Aerobic (Low Impact) on Blood Pressure in Hypertension Patients - Rohmah RAN; T I Puspita; Ikrima Rahmasari (LPPM Universitas Duta Bangsa Surakarta, 2019)
Hypertension is known as high blood pressure and is often referred to as a